ANALISIS FAKTOR – FAKTOR PENGHAMBAT PENERAPAN SERTIFIKAASI HALAL PETIS ROJORO (STUDI KASUS DI DESA KLAMPIS BARAT KECAMATAN KLAMPIS KABUPATEN BANGKALAN) - Rohmah, Wasilatur; Relanda Putra, Trischa; Rahayu Ningsih, Eni Sri (JISEF : Journal Of International Sharia Economics And Financial, 2024)
The purpose of this study was to analyze descriptively identify the factors inhibiting the implementation of halal certification of Petis Rojoro Hj.Nurmawaddah in West Klampis Village, Klampis District, Bangkalan Regency. The method used by researchers is descriptive qualitative research method and researchers make observations and observe directly on the object of research. The results showed that Petis Rojoro MSME is a micro, small and medium enterprise engaged in the seafood processing industry, especially petis. Petis rojoro Hj. Nur Mawaddah is one of the businesses that has been running from ancestors and until now it has developed rapidly to become part of the characteristics of West Klampis Village. The petis produced by Mrs. Hj. Nurhayati Al Mawaddah is made from processed sea fish, which is the main raw material, namely kaben fish and tuna and is the hallmark of this product. In the manufacturing process, the sea fish goes through various stages of processing involving boiling, drying, and fermentation to produce petis with a savory and thick taste that is very popular with the people of Bangkalan and Madura.